Pertumbuhan dan kelangsungan hidup benih ikan nila (Oreochromis niloticus) pada beberapa konsentrasi tepung daun jaloh (Salix tetrasperma) dalam pakan - Zuraidha Yanti; Zainal A. Muchlisin; Sugito (Depik Jurnal, 2013)
The objective of the present study was to evaluate the possibility of jaloh (Salix tetrasperma) leaf powders as alternative raw material for tilapia fish feed. Four concentrations of jaloh leafe powders (0%, 5%, 10% and 15%) were examined in this study. The experimental fish were fed three times a day on 08.00 AM, 12.00 AM and 17.00 PM. with feeding ration of 5% of body weight for 42 days. The one-way Anova test showed that the different concentrations of jaloh leaf powders gave a significantly effect on growth performance of tilapia larvae (p< 0.05), but did not give a significant effect on their survival rate (p>0.05). The Duncans test showed that the higher growth performace and survival rate were found at 5-10% of jaloh leaf powders, it was indicated that diet with 5-10% jaloh leaf powders were better than control (without jaloh leaf powders). Therefore, it is concluded that the jaloh leaf powders is suitable as alternative raws material for tilapia formulated diet at concentration of 5-10%.